Vitamin D decreases expression of NLRP1 and NLRP3 inflammasomes in placental explants from women with preeclampsia cultured with hydrogen peroxide - Nunes, Priscila R. [UNESP]; Romao-Veiga, Mariana [UNESP]; Matias, Mariana L. [UNESP]; Ribeiro, Vanessa R. [UNESP]; de Oliveira, Leandro [UNESP]; Peracoli, Jose Carlos [UNESP]; Terezinha S. Peracoli, Maria [UNESP] (Elsevier, 2022)
This study aimed to evaluate the immunomodulatory effect of vitamin D (VD) on the NLRP1 and NLRP3 inflammasomes in placental explants from preeclamptic (PE) and normotensive (NT) pregnant women. Placental explants from eight PE and eight NT pregnant women were cultured with or without hydrogen peroxide (H2O2), VD or H2O2 + VD. Gene and protein expression of NLRP1, NLRP3, HMGB1, caspase-1, IL-1β, TNF-α and IL-18 were determined by qPCR and Western blotting/ELISA. Compared to NT pregnant women, the endogenous gene expression of NLRP1, NLRP3, HMGB1, IL-1β, TNF-α and IL-18 was significantly higher in explants from PE and became decreased after VD treatment. Similarly, VD decreased the protein expression of NLRP1, NLRP3, caspase-1, HMGB1, IL-1β, TNF-α and IL-18 in PE. Placental explants from NT cultured with H2O2 showed increased gene and protein expression of NLRP1, NLRP3, caspase-1, IL-1β, TNF-α and HMGB1, while H2O2 was also able to increase TNF-α and caspase-1 gene expression in PE. Treatment with H2O2 + VD decreased gene/protein expression of NLRP1, NLRP3, caspase-1, HMGB1, IL-1β, TNF-α and IL-18 in PE and NT explants with H2O2. NLRP1 and NLRP3 are upregulated in the PE. VD may play an immunomodulatory role in the placental inflammation and downregulates oxidative stress induced in vitro by H2O2.
Keywords: Cytokines; Inflammasome; Placental explants; Preeclampsia; Vitamin D